Constitutional and ethical medical points of view on the importance of hospitalization of a patient with emergency cardiovascular pathology - S. S. Nesterov; Е. О. Taratukhin (Российский кардиологический журнал)
The article discusses the constitutional, ethical and medical aspects of hospitalization of patients with a life-threatening cardiovascular event. In itself, a medical condition is a complex biological event with many unpredictable aspects of its own course and adverse events and reactions in case of medical intervention. A doctor, as the central subject of medical care, faces four categories of difficulties: law, organizational, biomedical and ethical. Medical care is regulated by both article 41 of the Constitution of the Russian Federation and departmental acts of the health care system. Actually, doctor as a part of the healthcare system implement this right. The article provides an example of delivered judgment regarding complicated course of acute coronary syndrome. It shows the complexity of the medical situation, that regards the issues of doctor’s legal liability.